2015
DOI: 10.11648/j.jfns.20150306.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biofield Energy Treatment on Physical and Thermal Characteristics of Selenium Powder

Abstract: Selenium (Se) is an essential trace element, and its deficiency in the humans leads to increase the risk of various diseases, such as cancer and heart diseases. The objective of this study was to investigate the influence of biofield energy treatment on the physical and thermal properties of the selenium powder. The selenium powder was divided into two parts denoted as control and treated. The Control part was remained as untreated and treated part received Mr. Trivedi's biofield energy treatment. Both control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

9
0

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…The National Center of Complementary and Integrative Health (NCCIH) has been recognized and accepted Biofield Energy Healing as a Complementary and Alternative Medicine (CAM) health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, Tai Chi, Qi Gong, chiropractic/osteopathic manipulation, meditation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, relaxation techniques, hypnotherapy, healing touch, movement therapy, pilates, rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, Reiki, cranial sacral therapy and applied prayer (as is common in all religions, like Christianity, Hinduism, Buddhism and Judaism) [25]. The Biofield Energy Treatment (The Trivedi Effect ® ) has been extensively studied with significant outcomes in many scientific fields such as cancer research [26], altered antimicrobial sensitivity of pathogenic microbes in microbiology [27][28][29], biotechnology [30,31], genetics [32,33], changing the structure of the atom in relation to the various metals, ceramics, polymers and chemicals materials science [34][35][36], altered physical and chemical properties of pharmaceuticals [37,38], nutraceuticals [39,40], organic compounds [41][42][43], and improved overall growth and yield of plants in agricultural science [44,45]. Herbal extracts and herbal drugs despite of their outstanding in vitro results exhibited poor or negligible in vivo activity, because of their reduced lipid solubility or improper molecular size, causing deprived absorption and thus poor bioavailability [1].…”
Section: Introductionmentioning
confidence: 99%
“…The National Center of Complementary and Integrative Health (NCCIH) has been recognized and accepted Biofield Energy Healing as a Complementary and Alternative Medicine (CAM) health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, Tai Chi, Qi Gong, chiropractic/osteopathic manipulation, meditation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, relaxation techniques, hypnotherapy, healing touch, movement therapy, pilates, rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, Reiki, cranial sacral therapy and applied prayer (as is common in all religions, like Christianity, Hinduism, Buddhism and Judaism) [25]. The Biofield Energy Treatment (The Trivedi Effect ® ) has been extensively studied with significant outcomes in many scientific fields such as cancer research [26], altered antimicrobial sensitivity of pathogenic microbes in microbiology [27][28][29], biotechnology [30,31], genetics [32,33], changing the structure of the atom in relation to the various metals, ceramics, polymers and chemicals materials science [34][35][36], altered physical and chemical properties of pharmaceuticals [37,38], nutraceuticals [39,40], organic compounds [41][42][43], and improved overall growth and yield of plants in agricultural science [44,45]. Herbal extracts and herbal drugs despite of their outstanding in vitro results exhibited poor or negligible in vivo activity, because of their reduced lipid solubility or improper molecular size, causing deprived absorption and thus poor bioavailability [1].…”
Section: Introductionmentioning
confidence: 99%
“…The National Center of Complementary and Integrative Health (NCCIH) has been recognized and accepted Biofield Energy Healing as a Complementary and Alternative Medicine (CAM) health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, meditation, Qi Gong, Tai Chi, chiropractic/osteopathic manipulation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, hypnotherapy, relaxation techniques, pilates, healing touch, movement therapy, rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, cranial sacral therapy, Reiki, and applied prayer (as is common in all religions, like Hinduism, Buddhism, Christianity, and Judaism) [25]. The Biofield Energy Treatment (The Trivedi Effect ® ) has been extensively studied with significant outcomes in many scientific fields such as cancer research [26], biotechnology [27,28], genetics [29,30], altered antimicrobial sensitivity of pathogenic microbes in microbiology [31][32][33], altered structure of the atom in relation to the various metals, polymers, ceramics, and chemicals materials science [34][35][36], altered physical and chemical properties of organic compounds [37][38][39], pharmaceuticals [40,41], nutraceuticals [42,43], and improved overall growth and yield of plants in agricultural science [44,45]. Herbal extracts and it's formulations despite of their outstanding in vitro results exhibited poor or low in vivo activity, because of their low lipid solubility or improper molecular size, causing in deprived absorption and thus poor bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…The object or recipient always receives the energy from the ionosphere of the earth, the "universal energy field" and responds in a useful way. This process is known as The Trivedi Effect ® -Biofield Energy Healing Treatment [17,18] [20,21], cancer cells [22], plants [23,24], animals [25], medium [26,27], materials [28,29], pharmaceuticals [30,31], nutraceuticals [32,33], organic compounds [34,35]. The scientific study indicated that Biofield Energy Healing Treatment (The Trivedi Effect ® ) might be an alternate method for increasing or decreasing the natural isotopic abundance ratio of the substances [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%